EFFECT OF CULTIVARS, DATE, IBA AND THEIR INTERACTION ON ROOTING OF SEMI-HARDWOOD OLIVE CUTTING CVS. ’SHAMI ’ AND ’ QAISI - SAEED, GULALA M. A. (Journal of Duhok University, 2022)
This research was conducted during the growing season. (2016) in Bakrajo Nursery Station/ Sulaimani, Kurdistan Region-Iraq. Uniform and healthy olive (Olea europaea L.) Shami and Qaisi cuttings were used four concentrations (0, 1000, 2000, and 3000 ppm), three dates (15/3, 1/4, and 15/4) were used to investigate root growth of semi-hardwood olive cuttings cvs ’Shami’ and ’Qaisi’. The following is a summary of the findings: The IBA hormone treatment had a considerable impact on most root growth. On the majority of the root growth, Shami cv. significantly dominated than the Qaisi cvs. Most root growth characteristics were strongly impacted by interactions between date, IBA, and cv. Shami.